1990
DOI: 10.3382/ps.0690113
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Biological Value of Feed Phosphates for Chicks

Abstract: Two experiments were conducted to determine the relative biological values (BV) of phosphorus in feed phosphates. Experiment 2 was a replicate of Experiment 1, except that an additional phosphate source was tested. Within experiments, each treatment was replicated twice. Each pen contained eight broiler cockerels. The experimental diets were composed primarily of corn and soybean meal. The reference phosphate [anhydrous, reagent-grade, dibasic calcium phosphate (AR-DCP)] was added to supply five levels of phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…The MSP was not a commercial inorganic phosphate used for animals, but has often been used as a reference standard in animal experiments when the value of relative bioavailability of other P sources is determined (Nelson et al . ; Jongbloed et al . ; Cromwell ; Eeckhout & de Paepe ; Petersen et al .…”
Section: Discussionmentioning
confidence: 99%
“…The MSP was not a commercial inorganic phosphate used for animals, but has often been used as a reference standard in animal experiments when the value of relative bioavailability of other P sources is determined (Nelson et al . ; Jongbloed et al . ; Cromwell ; Eeckhout & de Paepe ; Petersen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that the P in DFP is slightly less available than that in commercial dicalcium phosphate for the chick (Peeler, 1972;Nelson et al, 1990) and the pig (Plumlee et al, 1958;Peeler, 1972;Cromwell et al, 19871, although some studies have shown the P in DFP and dicalcium phosphate to ET AL. be equally available (Hagemeier et al, 1981;Potter, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, these results are difficult to interpret because the birds grew better. Other reports (Nelson and Walker, 1964;Peeler, 1972;Nelson et al, 1990;Sullivan et al, 1992) using tibia bone ash as a response also found rock phosphate to have a lower P utilization than DCP. The exact reason is still unknown, but perhaps some unknown contamination or differences in solubility of HRP caused differences in the P and Ca contents of tibia and serum.…”
Section: Discussionmentioning
confidence: 90%